The Role of Knowledge Management in Managing Students' Creative Thinking Skills Using the Project Based Learning Model in the Era of Industrial Revolution 4.0 - Baiq Ertin Helmida,MP; Rosyia Wardani; Indah Arrifianti; Susilo Utomo (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to determine the effectiveness of implementing the Project Based Learning Model in improving creative thinking skills in Cirebon Regency High Schools and the differences between each school. The method used in this research is research and development or "Research and Development " ( R&D) using the Borg & Gall development research model with a quantitative approach. The population in this study were 5 high schools with 2 schools where testing was limited and 3 schools where testing was large. A total of 316 students were selected as samples using the purposive random sampling method in the experimental class and control class. Questionnaires are used to collect data. The validity of the instrument was confirmed using exploratory factor analysis, while reliability was estimated using Cronbach Alpha. Data were analyzed statistically with SPSS 21 using quantitative descriptive and Analysis of Variance (ANOVA). The research results show that the effectiveness of implementing the Project Based Learning Model is in the "very good" category, and there is no significant difference in the level of creative thinking abilities. The research results show that each school shows the same results in improving creative thinking skills with the appropriate level of effectiveness. Based on the research results, it is recommended to use the Project Based Learning Model for creative thinking skills for deeper learning in the future with the different characteristics of each school.